Effects of Tocilizumab Therapy on Serum Interleukin-33 and Interleukin-6 Levels in Patients With Rheumatoid Arthritis - In Ah CHOI; Sang Jin LEE; Won PARK; Sung Hwan PARK; Seung-cheol SHIM; Han Joo BAEK; Dae-Hyun YOO; Hyun Ah KIM; Soo Kon LEE; Yun Jong LEE; et al. (Archives of Rheumatology, 2018)
Objectives: This study aims to examine the effects of tocilizumab therapy on serum levels of interleukin (IL)-33 and IL-6 in rheumatoid arthritis (RA) patients. Patients and methods: Interleukin-33 and IL-6 levels in serum samples from 83 RA patients (10 males, 73 females; mean age 51.9 years; range, 26 to 77 years) and 12 healthy controls (2 males, 10 females; mean age 52.2 years; range, 39 to 62 years) were compared by cross-sectional, case control analysis. Of the RA patients, 40 received 24 weeks of tocilizumab therapy and were assigned to the prospective cohort. These 40 patients were then divided into two subgroups as responders and non-responders according to the American College of Rheumatology (ACR) 20. The remaining 43 RA patients did not receive tocilizumab therapy. Serum cytokine levels were analyzed at baseline and after 24 weeks of tocilizumab therapy in these patients. Results: Interleukin-33 and IL-6 concentrations were significantly higher in RA patients than in healthy controls (p<0.001 for both). Serum IL-33 levels in RA patients showed a significant correlation with rheumatoid factor titer (r=0.660, p<0.001), and IL-6 levels showed a significant correlation with high-sensitivity C-reactive protein levels (Spearman’s rank correlation coefficient=0.482, p<0.001). Serum IL-33 levels decreased significantly after 24 weeks of tocilizumab therapy (p<0.001); this was particularly marked in ACR20 responders (p<0.001). However, the decrease in non-responders was not significant (p=0.066). Changes in serum IL-6 levels after 24 weeks of tocilizumab therapy were not significant in either ACR20 responders or non-responders. Conclusion: Serum IL-33 levels in RA patients receiving tocilizumab therapy decreased significantly, particularly in ACR20 responders. Thus, IL-33 may be a useful marker for monitoring responses to tocilizumab therapy.